Factors affecting stock returns in the sub-sector companies of foods and beverages listed on the Indonesia Stock Exchange - Amalia Nur Fadhila; Desmiza Desmiza (President University, 2021)
Return is a result expected by investors when investing. This research aims to learn the effect of variable Debt to Asset Ratio, Total Asset Turn Over, Return on Asset, and Earning Per Share variables on Stock Return on the sub-sector companies of food and beverages listed on the Indonesia Stock Exchange period 2015-2019. The population that is used for this research amounts to 29 companies. The sampling technique used is the purposive method sampling, which led to the choosing of 17 companies that are used as the research sample. The methods that are used are descriptive and verificative methods with multiple panel data regression tests and Eviews program. The result of the analysis shows that Total Asset Turn Over has a positive impact on stock returns, while the Debt Asset Ratio, Return on Asset, and Earning per Share do not have an impact on stock returns.